Análise da produção leiteira no município de Dom Pedrito/RS. - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The dairy agribusiness is a fundamental department for the Brazilian agricultural economy it is one of the main activities developed in establishments classified as family economy. The city of Dom Pedrito, located inside the Rio Grande do Sul, in South Microregion, have in dairy production an important economic alternative for family farmers. In addition to enabling the utilization of family manpower, remunerates at market level allowing further that through their animals, the rural family has a store of value and (in some cases) high liquidity. But the production chain of national milk has undergone great changes in recent decades. The state even being one of the references in dairy production still faces many difficulties, presenting as major bottlenecks for dairy farming manpower, price of milk and the family succession. This study aimed to identify the main difficulties in dairy production of thirteen farmers in the city of Dom Pedrito / RS. As the nature of research was used the bibliographic research and in relation to the objectives was used the exploratory research. In addressing the problem, the research used the qualitative method also making a documentary analysis of data by questionnaire, as conducted by EMATER-RS Dom Pedrito, with thirteen dairy farmers in the municipality. Was held a discussion based on the results found in this group of family farmers in the dairy farming noting that producers of milk interviewed have manpower formed predominantly by family members. The management of the property is done by the owner himself, with ages ranging from 30 to 49 years. In the most part, farmers are illiterate or have incomplete elementary education which influence the management and control of business. The areas vary from 04 to 95 hectares of extension prevailing own areas. Among the main difficulties encountered as a result of this work are the lack of education of the farmer who manages the establishment, the lack of information on agricultural credit, uncertainty regarding the succession in the establishments, access to health, regularity of technical assistance, lack of government programs to ensure management training and improved productivity. The future of the dairy chain in the country, state and the municipality itself is promising, since it worked and resolved these difficulties
Keywords: Agricultura familiar; Produção leiteira; Dairy production; Family farming; CNPQ::CIENCIAS EXATAS E DA TERRA